Combination RC4 Algorithm and Base64 Encryption on The Least Significant Bit Method - Soleman, Soleman; Budiman, Dendi; Mubaroq, Sefty (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Steganography is an art form of hiding data or information on a medium. Steganography was created as a way to secure data by hiding it in other media so that it is